OC-002 Team simulation training for medical emergencies in the endoscopy unit. (28th May 2012) - Ray, S; Hills, K
Abstract : Introduction: Medical simulation is as an attractive way to practice clinical skills to improve confidence, teamwork and outcomes. 1 The endoscopy unit is an arena in which a heterogenous group of patients present with complex medical comorbidities. While emergencies are uncommon, they require prompt & seamless management. Simulation is common in industries such as aeronautics to practice rare but predictable incidents. Simulation is also used for teaching endoscopy. We therefore piloted novel simulation training in medical emergencies for our own unit's endoscopy staff (ES) before rolling this out across our trust in East Kent. Methods: We conducted three half-day sessions in a dedicated simulation complex. ES were divided into teams of two nurses and a healthcare assistant rotating through scenarios such as anaphylaxis and angina followed by feedback, tutorials & literature. The scenario room was equipped with a sophisticated mannequin capable of speech & respiration attached to monitoring including pulse, oxygen saturations & blood pressure manipulated from a control room. The room was fitted with cameras and microphones to assist feedback. There was a viewing chamber in which ES could watch their colleagues. Written candidate feedback was obtained. Results: In April 2010, six of our ES completed the pilot session. In September 2010 & 2011, 12 ES from two hospitals in our trust completed the session. None of the ES had ever had specific training in this area and were not confident in their abilities prior to the session. The vast majority found the training to be enjoyable, useful and that it enhanced their confidence. Conclusion: Simulation is becoming recognised as an important training tool in rehearsing responses to a variety of clinical settings. Our experience demonstrates that our ES did not feel confident in recognising and managing medical emergencies perhaps as they do not encounter them as frequently as ward nurses. The absence of such training is an omission in improving patient safety. The use of training in teams which work together on a daily basis helped reduce anxiety and improved confidence and the overall realism of the simulation. The staff strongly felt that this training was realistic and targetted to their learning needs and experience. While the use of our sophisticated simulation facility was advantageous in running our programme this is not critical to propagating this to other trusts. The mannequin and much of the equipment is portable and our next aim is to bring the simulation inside the endoscopy room to enhance realism and facilitate transfer to any endoscopy unit. Competing interests: None declared. Reference: 1. Ruesseler M, Weinlich M, Müller MP, et al. Simulation training improves ability to manage medical emergencies. Emerg Med J 2010;27 :734–8.